Réponses

2013-10-05T21:09:44+02:00
Bonjour c'est tres simple                                                                                                  F=3x(5x-12)-(5x-12)7=(5x-12)(3x-7)                                                                             G=(7x-8)(7x-8)+(7x-8)(4+9x)=(7x-8)(7x-8+4+9x)=(7x-8)(16x-4)=4('7x-8)(4x-1)                    H=(4x+9)(5x-4)-(7x-2)(4+9x)=pas possible                                                                  I=x2-18x+81=(x-9)2                                                                                               J=49-25x2=(7-5x)(7+5x) bon courage